Individual placement and support for ex-prisoners with mental health problems - Hamilton, Ian S. (2020)
Employment is often viewed by policymakers as a key factor in the reintegration process for ex-prisoners. This thesis centres around the examination of a specialist employment service, Individual Placement and Support (IPS), for ex-prisoners with mental health difficulties within the criminal justice system (CJS) in England and Wales. Specifically, this thesis seeks to understand what works, for whom, and under what circumstances. The key objectives of the study were to understand how the IPS service operated within the CJS, whether it was successful in achieving competitive employment for ex-prisoners with mental health difficulties, and how it may need to be adapted to improve its efficacy. In order to achieve this, the current study implemented a mixed-methods approach over a one-year timeframe. The recruitment of participants and delivery of the intervention was based within several prisons and across community sites within England.